2011
DOI: 10.1016/j.adolescence.2011.02.005
|View full text |Cite
|
Sign up to set email alerts
|

A closer look at co‐rumination: Gender, coping, peer functioning and internalizing/externalizing problems

Abstract: Co-rumination, defined as repetitive, problem-focused talk explains higher levels of friendship quality in youth (Rose, 2002) and increased levels of anxiety/depression in females. Middle adolescents (N=146) participated in a study of co-rumination, individual coping, externalizing/internalizing problems, and peer functioning. Consistent with past research, girls reported higher levels of co-rumination and internalizing symptoms. Co-rumination was also positively correlated with self-reports, but not teacher r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 49 publications
2
59
3
Order By: Relevance
“…Whereas interactions with peers are known to have increasing value during adolescence (Larson and Richards 1991), relationships with parents remain important to adolescents' affective functioning (Morris et al 2007). Notably, peer social support does not always serve a protective function for depression in young people (Auerbach et al 2011;Desjardins and Leadbeater 2011), and factors such as co-rumination can link peer social contexts with depressive and anxiety symptoms (Tompkins et al 2011). Family support is stably related to PA and NA in natural settings across adolescent development (Weinstein et al 2006), and support from fathers in particular has been observed as buffering the association between social stress and depressive symptoms over time (Desjardins and Leadbeater 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas interactions with peers are known to have increasing value during adolescence (Larson and Richards 1991), relationships with parents remain important to adolescents' affective functioning (Morris et al 2007). Notably, peer social support does not always serve a protective function for depression in young people (Auerbach et al 2011;Desjardins and Leadbeater 2011), and factors such as co-rumination can link peer social contexts with depressive and anxiety symptoms (Tompkins et al 2011). Family support is stably related to PA and NA in natural settings across adolescent development (Weinstein et al 2006), and support from fathers in particular has been observed as buffering the association between social stress and depressive symptoms over time (Desjardins and Leadbeater 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Additional characteristics of the individuals' social network such as number of friends and time spent using social networks and in depth demographics were also not assessed. Number of friends has been shown to be negatively related to personality factors such as shyness (Orr et al, 2009) and to corumination (Tompkins et al, 2011). Future research should expand upon details of individuals' social networks that could influence online behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…However, number of friends has been negatively associated with corumination in which individuals who coruminate more often have fewer friends. (Tompkins, Hockett, Abraibesh, & Witt, 2011). Research on corumination has also shown that the amount of corumination occurring in friendships was positively related to depression and anxiety (Rose et al, 2007).…”
Section: Psi Chi Journal Of Psychological Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, researchers have learned a great deal about the outcomes of co-rumination with studies producing consistent findings on the adjustment trade-offs (Calmes & Roberts, 2008;Rose, 2002;Rose et al, 2007;Starr & Davila, 2009;Tompkins, Hockett, Abraibesh, & Witt, 2011). Surprisingly, less is known about the predictors of co-rumination.…”
mentioning
confidence: 99%